2006
DOI: 10.1373/clinchem.2006.067181
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Changes in Metabolic Syndrome Abnormalities in US Adolescents: Findings from the 1988–1994 and 1999–2000 National Health and Nutrition Examination Surveys

Abstract: In the more recent dataset we explored the relationship between metabolic abnormalities and CRP as measured by a high-sensitivity assay. Results: The prevalence of central obesity, low HDLcholesterol, and hypertension increased between the 2 surveys. Three or more abnormalities (metabolic syndrome) were found in 12.7% [95% confidence interval (CI), 10.0%-15.4%] of fasting adolescents from the 1999 -2000 survey, compared with 9.2% (95% CI, 7.8%-10.6%; P <0.001) in the 1988 -1994 dataset, with increases also see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 32 publications
(33 reference statements)
10
103
0
5
Order By: Relevance
“…These results are in line with a similar finding in a huge survey of adolescents in USA and could be a further indicator of future cardiovascular risk. 32 Since carotid wall thickening has been demonstrated to reflect the presence of preclinical atherosclerotic disease at other sites, that is the coronary arteries, 33 and most importantly is an independent predictor of future cardiovascular events, 34 it could be useful to include carotid ultrasound assessment for the risk stratification of these children with MS.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with a similar finding in a huge survey of adolescents in USA and could be a further indicator of future cardiovascular risk. 32 Since carotid wall thickening has been demonstrated to reflect the presence of preclinical atherosclerotic disease at other sites, that is the coronary arteries, 33 and most importantly is an independent predictor of future cardiovascular events, 34 it could be useful to include carotid ultrasound assessment for the risk stratification of these children with MS.…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing evidence to show that chronic subclinical inflammation is associated with metabolic dysfunction, which links causally to insulin resistance and the metabolic syndrome in adolescents 77 . Dietary factors such as fatty acids, antioxidants or fibre can potentially modulate the association between adiposity and subclinical inflammation 78,79 , as can physical activity and fitness 80 , but more studies of the determinants of subclinical inflammation in this age group are needed to clarify how a healthier lifestyle affects these novel risk markers.…”
Section: Immunological Characteristics Related To Nutritional Statusmentioning
confidence: 99%
“…Studies have demonstrated that high CRP concentrations are associated with obesity in children [3,17,25] and in adults [13,18]. Correlations between CRP concentrations and high blood pressure or dyslipidaemia were found in children and adolescent [27].…”
Section: Discussionmentioning
confidence: 98%
“…In a prospective study, adiponectin predicted myocardial infarction in men [13]; however, more recent studies reveal mixed results [14,15]. Inflammatory markers such as interleukin-6 (IL-6) [16] and in particular C-reactive protein (CRP) are considered risk factors for the metabolic syndrome [17] and cardiovascular disease [7]. Fibrinogen, an acute-phase reactant that also plays a central role in the coagulation cascade, has been linked to obesity in adults [18] and children [19].…”
Section: Introductionmentioning
confidence: 99%